A Preconditioning Regimen with a PKCε Activator Improves Islet Graft Function in a Mouse Transplant Model. Issue 7 (July 2014) - Hamilton, Diana; Rugg, Caitlin; Davis, Nicolynn; Kvezereli, Manana; Tafti, Bashir Akhavan; Busque, Stephan; Fontaine, Magali
Transplantation of islets isolated from deceased donor pancreata is an attractive method of β-cell replacement therapy for patients with type 1 diabetes (T1D). However, the loss of islet cell viability and function during the peritransplant period is a limiting factor to long-term islet engraftment. Activation of the isoenzyme PKCe may improve islet survival and function. The current study assesses the effects of PKCe activation on islet graft function in a syngeneic streptozotocin-induced diabetic mouse model. Islets were isolated from wild-type BALB/c mice preconditioned with either a PKCe activator (ψεRACK) or a TAT carrier control peptide. Islets were further treated with the same agents during isolation, purification, and incubation prior to transplantation. Two hundred seventy-five islet equivalents were transplanted under the kidney capsule of streptozotocin-induced diabetic BALB/c mice. Islet function was assessed by measurement of blood glucose levels every 3 days for 42 days after transplant and through an intraperitoneal glucose tolerance test (IPGTT). The time for return to euglycemia in mice transplanted with islets treated with ψεRACK was improved at 14 ± 6 days versus 21 ± 6 days with TAT-treated islets. The IPGTT showed a 50% reduction in the area under the curve associated with an improved insulin response in mice transplanted with ψεRACK-treated islets compared to TAT-treated islets. A preconditioning regimen using PKCe agonist before pancreatic recovery and during islet isolation improves islet graft function and resistance to high glucose stress after transplantation.